IMPLEMENTATION OF CRITICAL INCIDENT TYPE ACTIVE LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS IN PRIVATE VOCATIONAL HIGH SCHOOLS BUILT BINA TARUNAN MEDAN MARELAN - Muhammad Ali Hanafiah, Leni Masnidar Nasution, Khairuddin YM, Darwis Margolang (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2020)
Abstract: The purpose of this study is to improve students' learning outcomes in Islamic religious education subjects through the application of the Critical Incidenttype Active Learningmodel. This type of research is qualitative research with a case study approach at SMK Bina Taruna Medan Marelan. The data collection method in this data collection uses observation, interview, and documentation techniques. The results showed that learning improved significantly. Thus it can be concluded that the application of critical incident type active learning model can improve student learning outcomes in Islamic subjects smk Bina Taruna Medan Marelan.